(untitled) - 1923-2005.; Berenstain, Stan; Berenstain, Jan; 1923-2012 (New York, 1971)
Big brown bear, blue bull, and beautiful baboon only encounter objects or meet people whose names begin with the letter B.
Keywords: Alphabet; Early chapter; Early readers